Proposed Design Graphs of Geotextile Reinforcement on Soft Clay under Various Field Conditions - Putu Tantri K. Sari; Yudhi Lastiasih; Sugiarto Sugiarto (Civil Engineering Dimension, 2016)
This paper describes the behavior of reinforced embankments constructed on soft clay subgrade with varying compressible depths, embankment slopes and embankment heights. The stability of the embankment is evaluated using the Bishop method. The resistance moment and the numbers of geotextiles required are examined. It is shown that varying the subgrade and embankment can significantly affect the embankment stability and also the number of reinforcements. It requires a lot of time to design embankment reinforcements, especially when the length of the embankment is tens of kilometers. The main aim of this study is to develop graphs to assist in designing the number of geotextile reinforcements. This paper proposes design graphs to support engineers and designers to determine the required geotextile reinforcements for embankments.